Historical Ecology of Cultural Keystone Places of the Northwest Coast. Issue 3 (5th July 2017) - Lepofsky, Dana; Armstrong, Chelsey Geralda; Greening, Spencer; Jackley, Julia; Carpenter, Jennifer; Guernsey, Brenda; Mathews, Darcy; Turner, Nancy J.
ABSTRACT: For many Indigenous peoples, their traditional lands are archives of their histories, from the deepest of time to recent memories and actions. These histories are written in the landscapes' geological features, contemporary plant and animal communities, and associated archaeological and paleoecological records. Some of these landscapes, recently termed "cultural keystone places" (CKPs), are iconic for these groups and have become symbols of the connections between the past and the future, and between people and place. Using an historical‐ecological approach, we describe our novel methods and initial results for documenting the history of three cultural keystone places in coastal British Columbia, Canada: Hauyat, Laxgalts'ap (Old Town) and Dałk Gyilakyaw (Robin Town) (territories of Heiltsuk, Gitga'ata, and Gitsm'geelm, respectively). We combine data and knowledge from diverse disciplines and communities to tell the deep and recent histories of these cultural landscapes. Each of CKPs encompasses expansive landscapes of diverse habitats transformed by generations of people interacting with their surrounding environments. Documenting the "softer" footprints of past human‐environmental interactions can be elusive and requires diverse approaches and novel techniques.